Service Innovation and Design: A Case Study of SMEs in the Tourism Sector - Azzahra Aurely Salsabilla Ardyani; Dian Puspita Sari; Fajar Widhiyatmoko; Ivan Arya Nugraha; Respati Amongrogo Dwi Wineka (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
This study explores the role of service innovation and design in enhancing the competitiveness of micro, small, and medium enterprises (MSMEs) in the tourism sector. In a market increasingly driven by experiences, service innovation has become a strategic tool not only for differentiation but also for fostering sustainable customer engagement. This journal adopts a qualitative approach using literature review and case synthesis methods, highlighting best practices and practical challenges faced by tourism MSMEs. The findings show that co-creation, personalization, digital integration, and service blueprinting significantly contribute to service improvement and customer satisfaction. The study concludes with concrete recommendations for MSMEs to redesign their service experiences in response to evolving consumer expectations and market trends.